Psoriatic erythroderma and hypothalamus-pituitary axis suppression due to misuse of systemic steroid: Two challenging cases - Gautam K Singh; Manas Chatterjee (Wolters Kluwer Medknow Publications, 2015)
Adding corticosteroid in homeopathic pills, self medication of steroid in the backdrop permanent cure in cases of psoriasis is not very uncommon in clinical practice in Indian subcontinent. First case a 52 year man, a known case of psoriasis vulgaris with psoriatic arthropathy of 15 years duration received multiple modalities of therapies without any satisfactory response. He was on self medication of tab prednisolone 10 mg daily with Cushingoid features. Second case a 22 year old boy, a known case of psoriasis from last 06 years was on Homeopathic treatment with Cushinoid features. Tapering of systemic steroid in first case and discontinuation of homeopathic drug in second case resulted in erythroderma and features of adrenal insufficiiency. Investigation revealed low morning cortisol and low cortisol following ACTH stimulation suggestive of HPA axis suppression. Planned withdrawal of steroid under the cover of short acting systemic steroid for short duration along with combination of immunosuppressants and supportive care gave an excellent result in both the cases.